Estimating deposit interest rate pass-through in central and Eastern European countries using wavelet transform and error correction model - Gábor Hajnal; Zsuzsanna Hosszú; Ákos Attila Ozoróczy; Bálint Dancsik (Magyar Nemzeti Bank, 2024)
Our study deals with interest rate pass-through for household and corporate deposits in the Central and Eastern European (CEE) region, focusing on the tightening cycle starting in the middle of 2021. This period is of particular interest for interest rate pass-through, as the sharp hikes by central banks in response to a high inflation environment followed a period characterised by a significant abundance of liquidity. We examine the relationship between interbank and deposit rates using two methods: wavelet transform and error-correction models. Based on the wavelet analysis, we found a weakening of pass-through and a slowdown in the repricing of deposit rates in the current tightening cycle among the countries of the CEE region, particularly in the household segment. Based on the error-correction models, in the sample including the tightening cycle, a weakening in the degree and speed of interest rate pass-through is consistently observed in the Hungarian and Polish deposit markets; and the extent of pass-through of the benchmark rate declined most in the Hungarian household deposit market among the CEE countries. Furthermore, a comparison of the interest rate paths estimated on the basis of the transmission correlations for the period excluding the tightening cycle starting in 2021 and the actual interest rate time series shows that the pass-through of the benchmark rate is the least efficient in the Hungarian household deposit market among the countries of the CEE region
Keywords: C51; C69; E32; E43; E52; 330; deposit interest rates; interest rate pass-through; wavelet transform; error-correction model